1979
DOI: 10.1080/03079457908418371
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some anticoccidial drugs on the development of immunity to coccidiosis in field and laboratory conditions

Abstract: SUMMARYIn a laboratory trial chickens were given immunising doses of six species of Eimeria when they were 2 weeks of age and the effect of medication with monensin or arprinocid from 0-10 weeks was determined by challenge inoculation. Monensin in the food at 60-100 ppm resulted in depression of immunity but concentrations of 40-50 ppm only slightly affected immunity to challenge inoculation. Arprinocid at 50 ppm also greatly reduced the development of resistance to infection but 20 ppm did not.In a field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In subsequent studies, immunity to various species of Eimeria was not prevented by monensin in some experiments but was strongly suppressed in others Karlsson and Reid, 1978). Not surprisingly, the degree of immunity was greater in birds given lower concentrations of the drug, a conclusion supported by the findings of Long et al (1979).…”
Section: Immunitymentioning
confidence: 64%
See 1 more Smart Citation
“…In subsequent studies, immunity to various species of Eimeria was not prevented by monensin in some experiments but was strongly suppressed in others Karlsson and Reid, 1978). Not surprisingly, the degree of immunity was greater in birds given lower concentrations of the drug, a conclusion supported by the findings of Long et al (1979).…”
Section: Immunitymentioning
confidence: 64%
“…In broiler breeder pullets fed ad libitum, monensin at a concentration of 110 mg/kg interfered with the development of immunity to Eimeria species but did not do so when birds were given a restricted feed intake regimen (Ruff and Chute, 1980). Suboptimal concentrations are often used to permit the development of immunity (Long et al, 1979). In the United States, monensin is not approved for use in laying chickens or birds more than 16 wk of age.…”
Section: Commercial Usementioning
confidence: 99%
“…Broadly speaking, ionophores in low concentration stimulate the immune response, and in higher doses have immunosuppressive effect [33, 42]. Long et al [28] found that monensin at 60–100 ppm reduced the immune response to infection with Eimeria , while concentration of 40 and 50 ppm allowed good development of immunity. Another ionophore, lasalocid, interferes partially with the development of immunity against E. tenella [39].…”
Section: Discussionmentioning
confidence: 99%
“…The drug(s) should minimize the effect of coccidiosis but allow some development of the parasite in order to stimulate a high degree of immunity. Long et al (1979) found that 40 to 50 mg monensin/kg allowed immunity to develop in replacement breeders, whereas 100 to 121 mg monensin/kg was needed to prevent coccidial disease losses in broilers. Immunity is important in flocks because it enhances overall coccidiosis control and will prevent occurrence of coccidiosis during the withdrawal period.…”
Section: Introductionmentioning
confidence: 99%